Pengaruh konseling menyusui terhadap sikap, motivasi dan keberhasilan ibu dalam menyusui di Desa Karangbong. - Mariani .; Nur Hamim (Universitas Sahid Surakarta, 2019)
Breastfeeding is a naturally occurring process, it is rare for a mother to fail or unable to breastfeed her baby. However, breastfeeding also needs to be studied primarily by mothers who first have children to know how to breastfeed properly. Despite the natural process, the mother's ability to breastfeed does not come suddenly, because there is a series of processes that contribute to the smoothness of breastfeeding, from the physical preparation to the inner mother. Counseling methods are the right approach used in health promotion at the individual level. Counseled individuals / groups have better awareness than those who are not getting counseling. Health workers should seek and conduct face-to-face meetings to provide accurate information and explain the false concepts of exclusive breastfeeding that occur in mothers. The purpose of this study is to determine the effect of breastfeeding counseling on maternal motivation, attitudes and success in breastfeeding. This research uses pre experimental design in the form of one group pre-post test. Sampling method used was total sampling with sample of breastfeeding mother in Karangbong Pajarakan Probolinggo village which fulfilled inclusion and exclusion criteria. This data was taken by using interview and observation, after tabulated data was tested using paired sample t-test through SPSS windows 12 program. The result showed that the attitude, motivation and success of the mother to breastfeed before being given counseling and after counseling showed a significant influence, where P = 0.000 is smaller than α = 0.005. So hopefully the implementation of breastfeeding counseling can continue to be encouraged, so that nursing mothers successfully breastfeed their babies and coverage of Exclusive breastfeeding can increase as expected.